Development of three-dimensional model for the analysis of the mass transport in vanadium redox flow batteries. (29th July 2022) - Yang, Fan; Qu, Dawei; Chai, Yuwei; Zhu, Mingyue; Fan, Luyan
Abstract: It is practical to equip the renewable energy system with the vanadium redox flow battery (VRFB) to improve energy utilization efficiency. A steady-stated, three-dimensional model is developed to study the flow and mass transfer in VRFB with serpentine flow field (SFF), and the corresponding experiments are also executed. The effect of the inlet flow rate on VRFB is analyzed by simulating the charge-discharge process, in which the uniformity factors, pressure drop, overpotential, protons concentration, and the battery efficiency are compared as indicators. Two split-SFFs are proposed to improve the pressure drop in the conventional SFF. The results show the efficiency of VRFB increase with the increase of the flow rate, but when the flow rate is higher than a critical flow rate, the performance on the VRFB is no longer sensitive to the flow rate. Compared to SFF, SFF(SY) performs well on pressure drop but poorly on discharge. Graphical abstract: Image 1 Highlights: A 3D model is developed to simulate the charge and discharge for VRFB. The relative error of voltages between simulations and experiments is 0.6127%. The optimal inlet flow rate could be predicted by the 3D model. Two split-SFFs are proposed to improve the pressure drop inside VRFB.